2023
DOI: 10.3390/microorganisms11020347
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid Composition, Antimicrobial Resistance and Virulence Genes Profiles of Ciprofloxacin- and Third-Generation Cephalosporin-Resistant Foodborne Salmonella enterica Isolates from Russia

Abstract: Salmonella enterica is an important foodborne pathogen worldwide. Ciprofloxacin and extended-spectrum cephalosporins are the common first-line antimicrobial drugs for the treatment of salmonellosis, antimicrobial resistance genes for which are mostly transferred via plasmids. The goal of this work was to perform genomic analysis of plasmids from foodborne S. enterica isolates obtained in Russia based on whole-genome sequencing. In the current study, 11 multidrug-resistant samples isolated in 2021 from 8 region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
2
3
0
Order By: Relevance
“…In this study, we used the unique combination of AMR genes, including blaCTX, to search over a half million Salmonella in NCBI PD for the clusters of environmental strains potentially carrying pESI plasmids. In addition to the two well described Salmonella Infantis clusters ESI-CTX-M-65 [9,12,13,19,20] and ESI-CTX-M-1 [5,9], we found two previously unreported Salmonella Infantis clusters carrying pESI ESI-CTX-M-14-1 and ESI-CTX-M-14-2 and two clusters of other serovars, although the isolates in some clusters had been described previously [11,28]. Among them, Salmonella Alachua strain with pESI plasmid has never been reported before.…”
Section: Discussionsupporting
confidence: 53%
“…In this study, we used the unique combination of AMR genes, including blaCTX, to search over a half million Salmonella in NCBI PD for the clusters of environmental strains potentially carrying pESI plasmids. In addition to the two well described Salmonella Infantis clusters ESI-CTX-M-65 [9,12,13,19,20] and ESI-CTX-M-1 [5,9], we found two previously unreported Salmonella Infantis clusters carrying pESI ESI-CTX-M-14-1 and ESI-CTX-M-14-2 and two clusters of other serovars, although the isolates in some clusters had been described previously [11,28]. Among them, Salmonella Alachua strain with pESI plasmid has never been reported before.…”
Section: Discussionsupporting
confidence: 53%
“…In this study, we used the unique combination of AMR genes, including blaCTX, to search over a half million Salmonella in NCBI PD for the clusters of environmental strains potentially carrying pESI plasmids. In addition to the two well described Salmonella Infantis clusters ESI-CTX-M-65 (9,12,13,19,20) and ESI-CTX-M-1(5, 9), we found two previously unreported Salmonella Infantis clusters carrying pESI ESI-CTX-M-14-1 and ESI-CTX-M-14-2 and two clusters of other serovars, although the isolates in some clusters had been described previously (11,28). Among them, Salmonella Alachua strain with pESI plasmid has never been reported before.…”
Section: Discussionsupporting
confidence: 51%
“…However, due to potential adverse effects, fluoroquinolones and aminoglycosides are not typically used in children [13]. Cephalosporins, especially the third-generation cephalosporins, are usually the drugs of choice for salmonellosis treatment in children [54]. The susceptibility tests showed that the rate of resistance to CRO was 10.4%, which was lower than that found in previous domestic studies conducted in children (24.5%, 37.4%, and 40.1% in Fujian, Zhejiang, and Guangdong Province, respectively) [33,38,45].…”
Section: Discussionmentioning
confidence: 99%